The Role of bFGF in the Excessive Activation of Astrocytes Is Related to the Inhibition of TLR4/NFκB Signals - Libing Ye (International Journal of Molecular Sciences, 2015)
Astrocytes have critical roles in immune defense, homeostasis, metabolism, and synaptic remodeling and function in the central nervous system (CNS); however, excessive activation of astrocytes with increased intermediate filaments following neuronal trauma, infection, ischemia, stroke, and neurodegenerative diseases results in a pro-inflammatory environment and promotes neuronal death. As an important neurotrophic factor, the secretion of endogenous basic fibroblast growth factor (bFGF) contributes to the protective effect of neuronal cells, but the mechanism of bFGF in reactive astrogliosis is still unclear. In this study, we demonstrated that exogenous bFGF attenuated astrocyte activation by reducing the expression of glial fibrillary acidic protein (GFAP) and other markers, including neurocan and vimentin, but not nestin and decreased the levels of pro-inflammatory cytokines, such as interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), via the regulation of the upstream toll-like receptor 4/nuclear factor κB (TLR4/NFκB) signaling pathway. Our study suggests that the function of bFGF is not only related to the neuroprotective and neurotrophic effect but also involved in the inhibition of excessive astrogliosis and glial scarring after neuronal injury.